ÁNFORAS Y MICROESPACIO EN TAMUDA. AVANCE DEL CONTEXTO MAURITANO DEL BARRIO ORIENTAL - Bernal-Casasola, Darío (Rei Cretariae Romanae Fautorum Acta, 2022)
The results of 2016-2018 archaeological field campaigns at the Eastern Quarter of the hellenistic site of Tamuda (northern Morocco) have offered a unique context with many complete amphorae from some Mauretanian buildings, abandoned in the first half of the 1st century BC. They include imported Italic Dressel 1 from Campania and other areas, Lamboglia 2, Brindisian ovoid amphorae and Late punic Ramon T-7.4.3.3 from Gades; together with local/regional ovoid Mauretanian amphorae and Ramon series 7 punic-shape vessels. Around 50 complete amphorae together with black gloss ware and other pottery items (lamps, common ware...) have been recovered. We will present for the first time this exceptional context, discussing the chronological scope and the micro-spatial analysis of the recovered finds, focusing on the local Mauretanian productions (complete examples of some types have been found).